KNOWLEDGE OF DISEASE AND ADHERENCE TO ANTI-TUBERCULOSIS TREATMENT-A CROSS SECTIONAL STUDY IN RAWALPINDI DISTRICT - Aziz, Dr. Kosar; Hisam, Dr. Aliya; Azam, Dr. Naila; Pervaiz, Dr. Farrah; Mahmood, Dr. Humaira (Pakistan Armed Forces Medical Journal, 2019)
Objective: The objective is to find out the knowledge regarding tuberculosis and patient‘s adherence to antituberculosis treatment and also to find out the association of adherence to anti-tuberculosis treatment with other social and demographic factors. Study Design: It was cross sectional study. Non probability convenient sampling technique was used. Place and Duration of Study: The study was carried out at Pak Emirates Military Hospital Rawalpindi, Tuberculosis Hospital Rawalpindi and Leprosy center Rawalpindi with effect, from Jan 2018 to Jan 2019. Patients and Methods: A total 366 patients of tuberculosis were included in the study. A structured questionnaire was prepared to assess the knowledge of disease (adequate and inadequate), and socio demographic variables. Morisky questionnaire was used to assess the adherence to treatment (High, Medium and Low). Results: Adequate knowledge was exhibited by 124 (35.5%) and 222 (65.5%) had inadequate knowledge about the disease. Forty four percent (123) low adherence to medication, 164(33%) medium and only 79 (21.6%) had high adherence to medication. Waiting time in the health care facility was reported <30 minutes by 174 (48%) of the respondents while 192 (52%) of the respondents reported a waiting time of greater than 30 minutes. It took more than 30 minutes to reach healthcare facility to more than 233 (63%) of the respondents and 277 (78%) complained about non availability of medicines. Conclusion: Adherence to treatment was inadequate in majority of the patients. A statistically significant association was found between knowledge and adherence, Other statistically significant factors included distance from the healthcare facility and between the waiting time at the facility and adherence. Low level of regular education and medicine not being readily available were other contributory factors.